Recycling and regenerating method for samarium-cobalt magnet waste

Through the hydrogen absorption and heat diffusion process of specific conditions, the complex, high cost and low efficiency of samarium-cobalt magnet waste recycling methods are solved, and high-performance samarium-cobalt magnets are efficiently recovered, simplifying the process flow and reducing costs.

CN119542016APending Publication Date: 2025-02-28HANGZHOU PERMANENT MAGNET GRP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411587088.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing samarium-cobalt magnet waste recycling methods have problems such as complex process flow, high cost, low recycling efficiency and inconsistent magnet performance, especially for the low recycling and treatment efficiency of 2:17 samarium-cobalt magnet waste.

Method used

The hydrogen absorption process and heat diffusion process with specific conditions are adopted, including processing the samarium-cobalt magnet waste into a substrate, performing hydrogen absorption treatment, forming a diffusion layer, and then diffusion heat treatment, supplementing samarium and copper elements, and improving the coercivity and squareness of the magnet.

Benefits of technology

The process flow is simplified, the cost is reduced, and the waste recycling efficiency is improved. The obtained samarium-cobalt magnet has high coercive force and Hk value, and the usage rate is close to 100%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005126058800000121
    Figure BDA0005126058800000121
Patent Text Reader

Abstract

The invention relates to a samarium-cobalt magnet waste recycling and regenerating method which comprises the following steps that samarium-cobalt magnet waste is processed into a samarium-cobalt magnet base body, and the residual magnetism of the samarium-cobalt magnet waste is larger than or equal to 11 kGs; the samarium-cobalt magnet base body is subjected to hydrogen absorption treatment at the normal temperature, a hydrogen absorption samarium-cobalt magnet is obtained, the hydrogen absorption treatment pressure ranges from 1 kPa to 10 kPa, and the hydrogen absorption treatment time ranges from 10 min to 60 min; the samarium-copper alloy slurry is placed on the surface of the hydrogen absorption samarium-cobalt magnet, a diffusion layer is formed after drying, then diffusion heat treatment is carried out, the diffused samarium-cobalt magnet is obtained, and the diffusion heat treatment process comprises the steps that heating is carried out to 750-900 DEG C, heat preservation treatment is carried out for 10-20 h, and then cooling is carried out to 350-450 DEG C at the speed of 0.3-0.7 DEG C / min; and processing the diffused samarium-cobalt magnet into a samarium-cobalt magnet finished product, wherein the thickness difference between the samarium-cobalt magnet substrate and the samarium-cobalt magnet finished product is less than 0.1 mm. According to the recycling and regenerating method for the samarium-cobalt magnet waste, the technological process is simplified, the cost is reduced, the waste recycling efficiency is high, and meanwhile the samarium-cobalt magnet obtained through regeneration has high coercive force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of samarium cobalt magnets, in particular to a method for recycling waste samarium cobalt magnets. Background Art

[0002] The main feature of SmCo magnets is their good high temperature resistance, which makes them suitable for use in high temperature environments. However, their production process is relatively sensitive, especially for the production of high-performance SmCo magnets. The suitable process range is relatively narrow. In addition, high-performance SmCo magnets are prone to copper depletion at the grain boundaries, which results in incomplete cell wall phases and the resulting magnet coercivity and H k Therefore, the qualified rate of samarium cobalt magnets is relatively low, and magnets with unqualified performance can only be treated as waste. If not handled properly, it will also cause pollution to the environment.

[0003] At present, there are mainly two methods for recycling waste samarium cobalt magnets. The first method is to use hydrogen crushing to make powder and reuse it in production to produce new samarium cobalt magnets. However, this method is suitable for the recycling of 1:5 samarium cobalt magnet waste. For the recycling of 2:17 samarium cobalt magnet waste, there are problems such as low hydrogen crushing efficiency and uneven mechanically crushed powder, which makes it difficult to ensure the consistency of magnet performance. The second method is to melt the samarium cobalt magnet waste and a certain proportion of raw materials together to achieve the purpose of recycling the samarium cobalt magnet waste, such as the treatment method adopted in patent CN105261474A. However, this method has a long process, complicated operation and high cost. Moreover, the proportion of smelted waste is only 20%-60%, and the efficiency of the entire treatment process is low. Summary of the invention

[0004] Based on this, it is necessary to provide a method for recycling waste samarium cobalt magnets to address the above problems. The method not only simplifies the process flow and reduces costs, but also has high waste recycling efficiency, and the regenerated samarium cobalt magnets have high coercivity.

[0005] A method for recycling samarium cobalt magnet waste comprises the following steps:

[0006] Processing samarium cobalt magnet waste into a samarium cobalt magnet matrix, wherein the residual magnetism of the samarium cobalt magnet waste is greater than or equal to 11 kGs;

[0007] The samarium cobalt magnet substrate is subjected to a hydrogen absorption treatment at room temperature to obtain a hydrogen absorption samarium cobalt magnet, wherein the hydrogen absorption treatment pressure is 1 kPa-10 kPa, and the hydrogen absorption treatment time is 10 min-60 min;

[0008] Placing samarium copper alloy slurry on the surface of the hydrogen absorbing samarium cobalt magnet, drying it to form a diffusion layer, and then performing diffusion heat treatment to obtain a diffused samarium cobalt magnet, wherein the diffusion heat treatment process includes: first heating to 750°C-900°C, keeping the temperature for 10h-20h, and then cooling to 350°C-450°C at a rate of 0.3 / min-0.7°C / min;

[0009] The diffused samarium cobalt magnet is processed into a samarium cobalt magnet finished product, wherein the difference in thickness between the samarium cobalt magnet matrix and the samarium cobalt magnet finished product is less than 0.1 mm.

[0010] In one embodiment, the residual magnetism of the samarium cobalt magnet waste is 11 kGs-12.5 kGs.

[0011] In one embodiment, the shape of the samarium cobalt magnet substrate is the same as the shape of the samarium cobalt magnet finished product;

[0012] And / or, the thickness of the samarium cobalt magnet matrix and the samarium cobalt magnet finished product are independently selected from 1 mm to 10 mm.

[0013] In one of the embodiments, the mass ratio of the samarium copper alloy slurry to the hydrogen absorbing samarium cobalt magnet is 1:200-1:100.

[0014] In one embodiment, the mass fraction of the samarium copper alloy in the samarium copper alloy slurry is 30%-70%;

[0015] And / or, in the samarium-copper alloy, the mass ratio of samarium to copper is 1:4-4:1.

[0016] In one embodiment, the diffusion layer has a thickness of 0.01 μm-0.1 μm.

[0017] In one embodiment, the diffusion heat treatment process further includes: cooling to 350°C-450°C, heat preservation for 2h-10h, and then cooling to room temperature.

[0018] In one embodiment, in the step of forming the diffusion layer after drying, the drying temperature is 80° C.-120° C., and the drying time is 5 min-20 min.

[0019] In one embodiment, in the step of processing samarium cobalt magnet waste into a samarium cobalt magnet matrix: the samarium cobalt magnet waste is cut, and then surface cleaning is performed, and the samarium cobalt magnet matrix is ​​obtained after drying, wherein the drying temperature is 80°C-150°C, and the drying time is 3min-10min.

[0020] In one embodiment, the method of placing the samarium copper alloy slurry on the surface of the hydrogen absorbing samarium cobalt magnet is selected from spraying, coating, screen printing, electroplating or physical vapor deposition;

[0021] And / or, in the step of processing the diffused samarium cobalt magnet into a finished samarium cobalt magnet product, the diffused samarium cobalt magnet is subjected to grinding, sandblasting and / or cleaning treatment in sequence to obtain the finished samarium cobalt magnet product.

[0022] The method for recycling and regenerating samarium cobalt magnet waste is aimed at recycling and regenerating samarium cobalt magnet waste with a high iron content, and the residual magnetism of the waste is above 11 kGs. By adopting a hydrogen absorption process and a thermal diffusion process under specific conditions, the grain boundary diffusion channel of the samarium cobalt magnet can be expanded while ensuring that the samarium cobalt magnet does not crack or break and does not destroy the crystal cellular structure of the samarium cobalt magnet, so that the samarium copper alloy can be fully diffused into the samarium cobalt magnet through the diffusion channel during the diffusion heat treatment process, and the samarium element lost in the production of the samarium cobalt magnet and the copper element in the copper-poor region of the grain boundary can be effectively supplemented, thereby improving the coercive force and squareness of the samarium cobalt magnet; at the same time, due to the conditions of the thermal diffusion process and the tempering process of the samarium cobalt magnet, the samarium copper alloy can be fully diffused into the samarium cobalt magnet through the diffusion channel during the diffusion heat treatment process, and the samarium copper alloy can be effectively supplemented. The conditions of the sequence are matched, so that diffusion and tempering are carried out simultaneously, which can avoid the adverse effect of the diffusion heat treatment process on the magnetic properties of the samarium cobalt magnet, and there is no need to set up an additional tempering process, thereby simplifying the process; since the samarium cobalt magnet is not broken during the hydrogen absorption treatment, there is no need for unnecessary powder making and molding sintering processes, thereby simplifying the process and reducing the production cost; and since the shape of the samarium cobalt magnet matrix is ​​the same as that of the samarium cobalt magnet finished product, and the thickness of the samarium cobalt magnet matrix and the samarium cobalt magnet finished product is basically the same, after the diffusion heat treatment process is completed, only simple post-treatment is required to obtain the samarium cobalt magnet finished product, and the utilization rate of the samarium cobalt magnet waste is basically 100%.

[0023] Therefore, the method for recycling waste samarium cobalt magnets of the present invention not only simplifies the process flow and reduces the cost, but also has high waste recycling efficiency, and the regenerated samarium cobalt magnets have high coercive force. DETAILED DESCRIPTION

[0024] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific implementation methods or embodiments, and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of related listed items, and the combinations include any two related listed items, any more related listed items, or all related listed items.

[0026] High-performance samarium cobalt magnets have a high iron content and their remanence can generally reach more than 11 kGs, but their performance qualification rate is low and they are prone to produce a large amount of waste. Therefore, the samarium cobalt magnet waste recycling method provided by the present invention is mainly aimed at the recycling and regeneration of samarium cobalt magnet waste with a high iron content, and the remanence of the waste is above 11 kGs, preferably the remanence of the samarium cobalt magnet waste is 11 kGs-12.5 kGs.

[0027] Specifically, the method for recycling samarium cobalt magnet waste of the present invention comprises the following steps:

[0028] S1, processing samarium cobalt magnet waste into a samarium cobalt magnet matrix, wherein the residual magnetism of the samarium cobalt magnet waste is greater than or equal to 11 kGs.

[0029] Specifically, in step S1, the samarium cobalt magnet waste is cut, and then the surface is cleaned and dried to obtain the samarium cobalt magnet matrix.

[0030] In one embodiment, the cutting method is selected from wire cutting, multi-wire cutting, electric spark cutting or laser cutting.

[0031] In one embodiment, the surface cleaning treatment may be carried out by ultrasonic cleaning, wherein the ultrasonic cleaning time is 5 min-20 min. Such a setting is conducive to better removing oil impurities on the surface of the samarium cobalt magnet and obtaining a clean samarium cobalt magnet matrix.

[0032] In one embodiment, the samarium cobalt magnet matrix may be in block or sheet shape, preferably in sheet shape.

[0033] Optionally, the drying temperature is 80° C.-150° C., and the drying time is 3 min-10 min.

[0034] S2, subjecting the samarium cobalt magnet substrate to a hydrogen absorption treatment at room temperature to obtain a hydrogen absorption samarium cobalt magnet, wherein the hydrogen absorption treatment pressure is 1 kPa-10 kPa, and the hydrogen absorption treatment time is 10 min-60 min.

[0035] Considering that it is difficult for samarium cobalt magnets to absorb hydrogen and the hydrogen breaking efficiency is low, generally samarium cobalt magnets will only break under high temperature and high pressure for a long time. It can be understood that the present invention performs hydrogen absorption treatment at room temperature and limits the hydrogen absorption treatment pressure and hydrogen absorption treatment time, that is, the hydrogen pressure is low and the hydrogen absorption time is short. Therefore, the present invention uses the hydrogen absorption process under the above specific conditions to perform hydrogen absorption treatment on the samarium cobalt magnet matrix, which will not cause the samarium cobalt magnet to crack and break, and can omit the powder making and molding sintering processes. Moreover, it can effectively expand the grain boundary diffusion channel of the high-performance samarium cobalt magnet, greatly reducing the difficulty of subsequent diffusion of samarium copper alloy.

[0036] Moreover, since the samarium cobalt magnet does not break during the hydrogen absorption treatment, there is no need for extra powder making and molding sintering processes, which reduces the production cost.

[0037] S3, placing samarium copper alloy slurry on the surface of the hydrogen absorbing samarium cobalt magnet, forming a diffusion layer after drying, and then performing diffusion heat treatment to obtain a diffused samarium cobalt magnet, wherein the diffusion heat treatment process includes: first heating to 750°C-900°C, keeping warm for 10h-20h, and then cooling to 350°C-450°C at a rate of 0.3 / min-0.7°C / min.

[0038] It can be understood that by using samarium copper alloy as the diffusion material, under the action of the diffusion heat treatment process under specific conditions, the samarium copper alloy can be fully diffused into the samarium cobalt magnet through the grain boundary diffusion channel of the samarium cobalt magnet, replenishing the samarium element content lost in the heat treatment of the samarium cobalt magnet, and replenishing the copper element in the copper-poor area of ​​the grain boundary, which is beneficial to achieve the integrity of the cell wall phase and improve the coercive force and squareness of the samarium cobalt magnet; and the copper element is beneficial to increase the fluidity of the grain boundary, making the samarium copper alloy diffuse more fully and evenly, further improving the coercive force and squareness of the samarium cobalt magnet, and improving the magnetic properties of the samarium cobalt magnet.

[0039] At the same time, the conditions of the thermal diffusion process of the present invention match the conditions of the tempering process of the samarium cobalt magnet, so that diffusion and tempering can be carried out simultaneously, which can avoid the adverse effects of the diffusion heat treatment process on the magnetic properties of the samarium cobalt magnet. At the same time, there is no need to set up an additional tempering process, which simplifies the process.

[0040] In step S3, the method of placing the samarium copper alloy slurry on the surface of the hydrogen absorbing samarium cobalt magnet is selected from spraying, coating, screen printing, electroplating or physical vapor deposition, wherein the physical vapor deposition method is selected from magnetron sputtering.

[0041] In one embodiment, the samarium copper alloy slurry is obtained by mixing samarium copper alloy powder, a dilution solution and a binder, wherein the mass ratio of the samarium copper alloy powder, the dilution solution and the binder is 30-70:100:1-2, the dilution solution is a polar solvent, and the polar solvent is selected from at least one of ethanol, n-propanol, isopropanol, propylene glycol, acetone, and polyethylene glycol, and the binder is selected from at least one of epoxy resin, polyvinyl butyral, and polyurethane.

[0042] Optionally, the mass ratio of the samarium copper alloy slurry to the hydrogen absorbing samarium cobalt magnet is 1:200-1:100; specifically, the mass ratio of the samarium copper alloy slurry to the hydrogen absorbing samarium cobalt magnet includes but is not limited to 1:200, 1:180, 1:160, 1:140, 1:120, 1:100. In this way, the diffusion and supplement effect of the samarium copper element can be further improved by adjusting the mass ratio of the samarium copper alloy slurry to the hydrogen absorbing samarium cobalt magnet, and the magnetic properties of the samarium cobalt magnet can be better improved, while avoiding the waste of samarium copper alloy.

[0043] Optionally, the mass fraction of the samarium copper alloy in the samarium copper alloy slurry is 30%-70%. Such a configuration is conducive to providing sufficient samarium copper elements and improving the magnetic properties of the samarium cobalt magnet.

[0044] Furthermore, in the samarium-copper alloy, the mass ratio of samarium to copper is 1:4-4:1. Specifically, the mass ratio of samarium to copper includes but is not limited to 1:4, 1:3, 1:2, 1:1, 2:1, 3:1, 4:1. Such a configuration is conducive to improving the magnetic properties of the samarium-cobalt magnet.

[0045] Optionally, the drying temperature is 80° C.-120° C., and the drying time is 5 min-20 min. Such an arrangement is conducive to forming a diffusion layer with uniform density.

[0046] Furthermore, the thickness of the diffusion layer is 0.01 μm-0.1 μm. Specifically, the thickness of the diffusion layer includes but is not limited to 0.01 μm, 0.02 μm, 0.03 μm, 0.04 μm, 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, and 0.1 μm. Such a configuration is conducive to better achieving uniform diffusion of samarium and copper elements into the samarium cobalt magnet through the diffusion channel during the diffusion heat treatment process, thereby further improving the magnetic properties of the samarium cobalt magnet.

[0047] Optionally, the diffusion heat treatment process further comprises: cooling to 350°C-450°C, heat preservation for 2h-10h, and then cooling to room temperature. Such an arrangement is conducive to better improving the magnetic properties of the samarium cobalt magnet.

[0048] S4, processing the diffused samarium cobalt magnet into a finished samarium cobalt magnet product, wherein a difference in thickness between the samarium cobalt magnet matrix and the finished samarium cobalt magnet product is less than 0.1 mm.

[0049] It can be understood that in the present invention, by controlling the difference in thickness between the samarium cobalt magnet matrix and the samarium cobalt magnet finished product, the size of the samarium cobalt magnet matrix and the samarium cobalt magnet finished product are made substantially the same. Therefore, in the present invention, after the diffusion heat treatment is completed, a simple post-treatment is performed to obtain the samarium cobalt magnet finished product, and the performance of the samarium cobalt magnet finished product can be more effectively controlled. There is no need to prepare the samarium cobalt magnet through conventional production processes of samarium cobalt magnets, such as smelting, powder making, molding, isostatic pressing, sintering and other processes, which simplifies the process and reduces the cost.

[0050] Moreover, in the present invention, the utilization rate of samarium cobalt magnet waste is substantially 100%, which further reduces the recycling cost and saves resources.

[0051] Therefore, the method for recycling waste samarium cobalt magnets of the present invention not only simplifies the process flow and reduces the cost, but also has high waste recycling efficiency, and the regenerated samarium cobalt magnets have high coercive force.

[0052] In addition, compared with crushing the samarium cobalt magnet waste and then mixing it with the samarium copper alloy powder and then performing thermal diffusion, the overall process flow of the samarium cobalt magnet waste treatment in the present invention is less, and the amount of samarium copper alloy used, especially samarium, is less, the processing cost is lower, and the recovery efficiency is higher, which is suitable for promotion in enterprise production.

[0053] In the present invention, the shape of the samarium cobalt magnet substrate and the shape of the samarium cobalt magnet finished product may be the same or different, but are preferably the same.

[0054] In one embodiment, the shapes of the samarium cobalt magnet matrix and the samarium cobalt magnet product are independently selected from a square shape, a cylindrical shape or a circular ring shape.

[0055] Optionally, the thickness of the samarium cobalt magnet matrix is ​​1mm-10mm; the thickness of the samarium cobalt magnet finished product is 1mm-10mm. Such an arrangement not only allows the diffusion alloy elements to enter the grain boundaries of the entire samarium cobalt magnet matrix during the thermal diffusion process, thereby improving the diffusion effect, but also avoids multiple processing, reduces processing costs, and reduces the risk of cracking caused by magnet processing.

[0056] In step S4, the diffused samarium cobalt magnet is subjected to grinding, sandblasting and / or cleaning in sequence to obtain a finished samarium cobalt magnet. In this way, the diffusion layer remaining on the surface of the samarium cobalt magnet that has not been completely diffused can be removed, and a finished samarium cobalt magnet with high quality, good appearance and uniform size can be obtained.

[0057] The following specific examples will be used to further illustrate the samarium cobalt magnet waste recycling method. However, it will be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0058] Example 1

[0059] The waste samarium cobalt magnet with a residual magnetism of about 11.2 kGs is cut into cylindrical samarium cobalt magnets with a diameter of 10 mm and a thickness of 5.05 mm by multi-wire cutting; the cut samarium cobalt magnet is ultrasonically cleaned for 10 minutes to remove surface oil and impurities, and then placed in an oven at 100°C for 5 minutes and then taken out to obtain a dried samarium cobalt magnet; then the dried samarium cobalt magnet is placed in a hydrogen furnace for hydrogen absorption treatment at room temperature to obtain a hydrogen absorbing samarium cobalt magnet, wherein the hydrogen pressure is 5 kPa and the hydrogen absorption time is 30 minutes.

[0060] The samarium copper alloy slurry is sprayed on the surface of the hydrogen absorbing samarium cobalt magnet, and the diffusion layer is formed after being kept in an oven at 100°C for 20 minutes, wherein the mass ratio of the samarium copper alloy slurry to the hydrogen absorbing samarium cobalt magnet is 1:150, the mass fraction of the samarium copper alloy in the samarium copper alloy slurry is 50%, and the mass ratio of samarium to copper in the samarium copper alloy is 7:3, and the thickness of the diffusion layer is 0.06 μm; then the samarium cobalt magnet with the diffusion layer formed is placed in a vacuum heat treatment furnace Diffusion heat treatment is carried out to allow the samarium copper alloy to diffuse into the interior of the samarium cobalt magnet, and the magnet is cooled to room temperature and taken out of the furnace to obtain a diffused samarium cobalt magnet. The diffusion heat treatment process includes: first heating to 860°C for 15 hours, then cooling to 400°C at a rate of 0.5°C / min for 4 hours; the diffused samarium cobalt magnet is ground, sandblasted and cleaned to obtain a finished samarium cobalt magnet with a thickness of 5.0 mm.

[0061] Example 2

[0062] The samarium cobalt magnet waste with a residual magnetism of about 11.6 kGs is cut into cylindrical samarium cobalt magnets with a diameter of 10 mm and a thickness of 5.02 mm by a multi-wire cutting method; the cut samarium cobalt magnet is ultrasonically cleaned for 10 minutes to remove surface oil and impurities, and then placed in an oven at 100°C for 5 minutes and then taken out to obtain a dried samarium cobalt magnet; then the dried samarium cobalt magnet is placed in a hydrogen furnace for hydrogen absorption treatment at room temperature to obtain a hydrogen absorbing samarium cobalt magnet, wherein the hydrogen pressure is 5 kPa and the hydrogen absorption time is 20 minutes.

[0063] The samarium copper alloy slurry is sprayed on the surface of the hydrogen absorbing samarium cobalt magnet, and the diffusion layer is formed after being kept in an oven at 100°C for 20 minutes, wherein the mass ratio of the samarium copper alloy slurry to the hydrogen absorbing samarium cobalt magnet is 1:200, the mass fraction of the samarium copper alloy in the samarium copper alloy slurry is 30%, and the mass ratio of samarium to copper in the samarium copper alloy is 1:1, and the thickness of the diffusion layer is 0.02 μm; then the samarium cobalt magnet with the diffusion layer formed is placed in a vacuum heat treatment furnace Diffusion heat treatment is carried out to allow the samarium copper alloy to diffuse into the interior of the samarium cobalt magnet, and the samarium cobalt magnet is cooled to room temperature and taken out of the furnace to obtain a diffused samarium cobalt magnet. The diffusion heat treatment process includes: first heating to 830°C for 15 hours, then cooling to 400°C at a rate of 0.5°C / min for 4 hours; the diffused samarium cobalt magnet is ground, sandblasted and cleaned to obtain a finished samarium cobalt magnet with a thickness of 5.0 mm.

[0064] Example 3

[0065] The samarium cobalt magnet waste with a residual magnetism of about 12.0 kGs is cut into cylindrical samarium cobalt magnets with a diameter of 10 mm and a thickness of 5.08 mm by a multi-wire cutting method; the cut samarium cobalt magnet is ultrasonically cleaned for 10 minutes to remove surface oil and impurities, and then placed in an oven at 100°C for 5 minutes and then taken out to obtain a dried samarium cobalt magnet; then the dried samarium cobalt magnet is placed in a hydrogen furnace for hydrogen absorption treatment at room temperature to obtain a hydrogen absorbing samarium cobalt magnet, wherein the hydrogen pressure is 5 kPa and the hydrogen absorption time is 10 minutes.

[0066] The samarium copper alloy slurry is sprayed on the surface of the hydrogen absorbing samarium cobalt magnet, and the diffusion layer is formed after being kept in an oven at 100°C for 20 minutes, wherein the mass ratio of the samarium copper alloy slurry to the hydrogen absorbing samarium cobalt magnet is 1:100, the mass fraction of the samarium copper alloy in the samarium copper alloy slurry is 70%, and the mass ratio of samarium to copper in the samarium copper alloy is 3:7, and the thickness of the diffusion layer is 0.1 μm; then the samarium cobalt magnet with the diffusion layer formed is placed in a vacuum heat treatment furnace for Diffusion heat treatment is performed to allow the samarium copper alloy to diffuse into the interior of the samarium cobalt magnet, and the samarium cobalt magnet is cooled to room temperature and taken out of the furnace to obtain a diffused samarium cobalt magnet. The diffusion heat treatment process includes: first heating to 800°C for 15 hours, then cooling to 400°C at a rate of 0.5°C / min for 4 hours; the diffused samarium cobalt magnet is ground, sandblasted and cleaned to obtain a finished samarium cobalt magnet with a thickness of 5.0 mm.

[0067] Example 4

[0068] Compared with Example 1, Example 4 differs only in that the mass ratio of the samarium copper alloy slurry to the hydrogen absorbing samarium cobalt magnet is 1:300, the thickness of the diffusion layer is 0.01 μm, and the other conditions are the same, and a finished samarium cobalt magnet with a thickness of 5.0 mm is obtained.

[0069] Example 5

[0070] The only difference between Example 5 and Example 1 is that the mass fraction of the samarium copper alloy in the samarium copper alloy slurry is 10%, and the other conditions are the same, and a finished samarium cobalt magnet with a thickness of 5.0 mm is obtained.

[0071] Example 6

[0072] The only difference between Example 6 and Example 1 is that the mass ratio of samarium to copper in the samarium-copper alloy is 1:5, and the other conditions are the same, and a finished samarium-cobalt magnet with a thickness of 5.0 mm is obtained.

[0073] Example 7

[0074] The only difference between Example 7 and Example 1 is that the mass ratio of samarium to copper in the samarium-copper alloy is 5:1, and the other conditions are the same, and a finished samarium-cobalt magnet with a thickness of 5.0 mm is obtained.

[0075] Comparative Example 1

[0076] The difference between Comparative Example 1 and Example 1 is that the residual magnetism of the samarium cobalt magnet waste is about 10.0 kGs, and the other conditions are the same, and a samarium cobalt magnet product with a thickness of 5.0 mm is obtained.

[0077] Comparative Example 2

[0078] The only difference between Comparative Example 2 and Example 1 is that in the hydrogen absorption treatment step, the hydrogen absorption temperature is 200°C and the hydrogen absorption treatment pressure is 20 kPa, and the other conditions are the same. The comparative example cannot obtain a finished samarium cobalt magnet because the dried samarium cobalt magnet absorbs a large amount of hydrogen under high temperature and high pressure, which makes its internal stress larger and brittle, resulting in it being broken during grinding after the diffusion heating treatment.

[0079] Comparative Example 3

[0080] The only difference between Comparative Example 3 and Example 1 is that in the hydrogen absorption treatment step, the hydrogen absorption treatment pressure is 0.5 kPa, and the other conditions are the same, and a finished samarium cobalt magnet with a thickness of 5.0 mm is obtained.

[0081] Comparative Example 4

[0082] The difference between Comparative Example 4 and Example 1 is that the diffusion heat treatment process is: first heating to 950°C, keeping warm for 10h-20h, and then cooling to 350°C-450°C at a rate of 0.3 / min-0.7°C / min. The other conditions are the same, and a finished samarium cobalt magnet with a thickness of 5.0mm is obtained.

[0083] Comparative Example 5

[0084] The only difference between Comparative Example 5 and Example 1 is that the temperature is lowered to 400° C. at a rate of 0.1° C. / min, and the other conditions are the same, thereby obtaining a finished samarium cobalt magnet with a thickness of 5.0 mm.

[0085] Comparative Example 6

[0086] The only difference between Comparative Example 6 and Example 1 is that the temperature is lowered to 400° C. at a rate of 1.0° C. / min, and the other conditions are the same, thereby obtaining a finished samarium cobalt magnet with a thickness of 5.0 mm.

[0087] The magnetic properties of the samarium cobalt magnets prepared in Examples 1-7 and Comparative Examples 1-6 were tested respectively, and the test results are shown in Table 1, wherein the test method is as follows: a Magnet-Physik EP5 hysteresis loop measuring instrument is used to measure the demagnetization curve and various magnetic property parameters of the finished samarium cobalt magnets, that is, the finished samarium cobalt magnets obtained in the examples and comparative examples are directly placed in the measuring coil.

[0088] It should be noted that, since the finished samarium cobalt magnets prepared in the embodiments and comparative examples of the present invention are relatively small in size, there is no need to perform hole-digging for sampling, and therefore, they can be directly placed in the measuring coil.

[0089] Table 1

[0090]

[0091]

[0092] It can be seen from the data in Table 1 that the present invention uses a synergistic relationship of a hydrogen absorption process and a thermal diffusion process under specific conditions and limiting the thickness difference between the samarium cobalt magnet matrix and the samarium cobalt magnet finished product to be less than 0.1 mm, so that when the present invention processes the recycling and regeneration of high-performance samarium cobalt magnet waste with a high iron content, it not only simplifies the process flow and reduces the cost, but also has a high waste recycling efficiency, and the regenerated samarium cobalt magnet has a high coercive force and H k .

[0093] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0094] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for recycling waste samarium cobalt magnets, characterized in that: The steps include: Processing samarium cobalt magnet waste into a samarium cobalt magnet matrix, wherein the residual magnetism of the samarium cobalt magnet waste is greater than or equal to 11 kGs; The samarium cobalt magnet substrate is subjected to a hydrogen absorption treatment at room temperature to obtain a hydrogen absorption samarium cobalt magnet, wherein the hydrogen absorption treatment pressure is 1 kPa-10 kPa, and the hydrogen absorption treatment time is 10 min-60 min; Placing samarium copper alloy slurry on the surface of the hydrogen absorbing samarium cobalt magnet, drying it to form a diffusion layer, and then performing diffusion heat treatment to obtain a diffused samarium cobalt magnet, wherein the diffusion heat treatment process includes: first heating to 750°C-900°C, keeping the temperature for 10h-20h, and then cooling to 350°C-450°C at a rate of 0.3 / min-0.7°C / min; The diffused samarium cobalt magnet is processed into a samarium cobalt magnet finished product, wherein the difference in thickness between the samarium cobalt magnet matrix and the samarium cobalt magnet finished product is less than 0.1 mm.

2. The method for recycling samarium cobalt magnet waste according to claim 1, characterized in that: The residual magnetism of the samarium cobalt magnet waste is 11 kGs-12.5 kGs.

3. The method for recycling samarium cobalt magnet waste according to claim 1, characterized in that: The shape of the samarium cobalt magnet matrix is ​​the same as the shape of the samarium cobalt magnet finished product; And / or, the thickness of the samarium cobalt magnet matrix and the samarium cobalt magnet finished product are independently selected from 1 mm to 10 mm.

4. The method for recycling samarium cobalt magnet waste according to claim 1, characterized in that: The mass ratio of the samarium copper alloy slurry to the hydrogen absorbing samarium cobalt magnet is 1:200-1:

100.

5. The method for recycling samarium cobalt magnet waste according to claim 4, characterized in that: The mass fraction of the samarium copper alloy in the samarium copper alloy slurry is 30%-70%; And / or, in the samarium-copper alloy, the mass ratio of samarium to copper is 1:4-4:

1.

6. The method for recycling samarium cobalt magnet waste according to claim 1, characterized in that: The diffusion layer has a thickness of 0.01 μm-0.1 μm.

7. The method for recycling waste samarium cobalt magnets according to claim 1, characterized in that: The diffusion heat treatment process also includes: cooling to 350° C.-450° C., heat preservation for 2 h-10 h, and then cooling to room temperature.

8. The method for recycling samarium cobalt magnet waste according to claim 1, characterized in that: In the step of forming a diffusion layer after drying, the drying temperature is 80° C.-120° C., and the drying time is 5 min-20 min.

9. The method for recycling waste samarium cobalt magnets according to claim 1, characterized in that: In the step of processing samarium cobalt magnet waste into a samarium cobalt magnet matrix: the samarium cobalt magnet waste is cut, and then surface cleaning treatment is performed, and after drying, the samarium cobalt magnet matrix is ​​obtained, wherein the drying temperature is 80° C.-150° C., and the drying time is 3 min-10 min.

10. The method for recycling samarium cobalt magnet waste according to claim 1, characterized in that: The method of placing the samarium copper alloy slurry on the surface of the hydrogen absorbing samarium cobalt magnet is selected from a spraying method, a coating method, a screen printing method, an electroplating method or a physical vapor deposition method; And / or, in the step of processing the diffused samarium cobalt magnet into a finished samarium cobalt magnet product, the diffused samarium cobalt magnet is subjected to grinding, sandblasting and / or cleaning treatment in sequence to obtain the finished samarium cobalt magnet product.

Citation Information

Patent Citations

  • Method for recycling samarium-cobalt permanent magnet material waste

    CN105261474A